Gait instability, ophthalmoplegia, and chorea with orofacial dyskinesia in a man with anti-Ri antibodies: a case report - Shioda, Mukuto; Fujita, Hiroaki; Onuma, Hiroki; Sakuramoto, Hirotaka; Hamaguchi, Mai; Suzuki, Keisuke (Frontiers in Neurology, 2024)
A 79-year-old man was admitted for 2 weeks of dizziness, followed by diplopia, involuntary movement and progressive gait disturbances. Neurologic examination revealed horizontal and vertical gaze paresis, bilateral choreiform movement with orofacial dyskinesia, and limb/truncal ataxia. MRI revealed fluid-attenuated inversion recovery image-hyperintense signal abnormalities in the dorsal midbrain, pontine and medulla. Within another few days, the patient developed type II acute respiratory failure requiring artificial invasive ventilation. Because autoimmune encephalitis was suspected, he received intravenous immunoglobulin therapy followed by intravenous methylprednisolone, but only his ophthalmoplegia improved minimally. Serological tests were positive for anti-Ri onconeural antibodies. CT-guided mediastinal lymph node biopsy was performed and revealed small cell lung carcinoma. We report the rare manifestation of anti-Ri antibody-associated paraneoplastic neurological syndrome (PNS), and this case can alert us to the importance of respiratory management in this diverse neurologic disease. Furthermore, PNSs positive for anti-Ri antibodies should be added to the list of differential diagnoses of chorea with orofacial dyskinesia.